Circulating chemokine ligand levels before and after successful kidney transplantation. Issue 1 (December 2016) - Elmoselhi, Hamdi; Mansell, Holly; Soliman, Mahmoud; Shoker, Ahmed
Abstract Background Chemokine ligands (CCLs) play a pivotal role in tissue injury before and after kidney transplantation. Meanwhile, transplantation improves patient's survival and diminishes morbidity. It is hypothesized, then, that kidney transplantation diminishes pre-transplant (pre-TX) levels of circulating inflammatory CCLs. This retrospective study compared circulating levels and profiles of CCLs before transplantation (pre-TX) and after transplantation (post-TX). Methods Nineteen CCLs (1, 2, 3, 4, 5, 8, 11, 13, 15, 17, 21, 24, 26, 27, CXCL 5, 8, 10, 12 and 13) were measured in 47 stable post-TX recipients, and their stored pre-TX plasma was analyzed by multiplexed fluorescent bead-based immunoassay. Twenty normal controls were included for comparisons. Normalized data was presented as mean ± SD and non-normalized data as median (5–95 % CI). Significance was measured at p < 0.01. Arbitrary upper and lower margins for each CCL at the 95 % CI or 2SD levels in each group were chosen to calculate the percentile of patients in the other group who exceeded these limits. Significant CCL levels present in more than 75 % of patients in a group that exceeded the arbitrary upper or lower set margins in the other two groups were labeled as preferentially characteristic for the respective group. Results More than 75 % of pre- and post-TX patients had levels that exceeded the upper control for CCL1, 11, 15 and CCL15, CCL26 and CXCL13 levels, respectively. More than 75 % of pre- and post-TX patients exceeded the lower control for CCL3, 21, and CCL5 limits, respectively. More than 75 % of post-TX patients demonstrated elevated levels of CCL2, 3, 21, 26 and CXCL13 above the upper pre-TX cut offs. Meanwhile, more than 75 % of post-TX patients exceeded the lower pre-TX levels for CCL1, 4, 5, 8, 13, 15, 17, 24 and CXCL8 and10. Pre-TX was preferentially characterized by elevated CCL1 and 15 and diminished CCL3 and 21. Post-TX was preferentially characterized by elevated CCL26 and CXCL13 and diminished CCL4 and 5. Conclusion End stage kidney disease is associated with enhanced circulating inflammatory chemokine levels. Stable kidney transplantation is associated with 1) lowered burden of circulating inflammatory chemokine levels and, 2) elevation in the pro T-helper2 chemokine, CCL26 and the homeostatic CXCL13.